Analysis on spatio-temporal evolution and influencing factors of ecosystem service in the Changsha-Zhuzhou-Xiangtan urban agglomeration, China - Huang, Xuanhua; Xie, Youping; Lei, Fan; Cao, Li; Zeng, Haibo (Frontiers in Environmental Science, 2024)
Introduction: It is of great significance to strengthen the evaluation research and driving force analysis of ecosystem services value for the rational utilization and protection of the ecological environment of Changsha-Zhuzhou-Xiangtan (CZT) urban agglomeration and the promotion of the integration of urban agglomeration. Methods: Based on the remote sensing image data, the spatial and temporal evolution characteristics and influencing factors of the ecosystem services value of CZT urban agglomeration were analyzed by the methods of ArcGIS10.2, Geoda, value equivalent and spatial statistics. Results: The results showed that: 1) From 2000 to 2020, the total value of ecosystem service in the CZT urban agglomeration decreased gradually, with an overall decrease of 4,381.07 × 106 yuan. In the past 20 years, the ecosystem service Value (ESV) of cultivated land, forest land and grassland had declined, but the ESV of water area and unused land had fluctuated, and the single ESV had declined. 2) From 2000 to 2020, the spatial distribution of ESV in the CZT urban agglomeration showed an obvious pattern of “low in the middle and high in the surrounding areas”, and the changes were quite different in different periods. 3) The spatial correlation between ESV and distance from county government, distance from railway, proportion of construction land, NDVI, population density, economic density, slope and precipitation were significant. The spatial distribution of the distance from the county government, the distance from the railway, NDVI and ESV were similar; the population density and economic density were consistent with the spatial distribution of ESV; and the spatial distribution of construction land proportion, slope, precipitation and ESV were different. Discussion: The results of the study can provide some reference for the further development of ecological protection policies and related planning in urban agglomerations.